Composite control system of hybrid-driven mid-altitude airship. (7th December 2017) - Chen, L.; Dong, Q.; Zhang, G.; Duan, D.
ABSTRACT: In general, an airship is equipped with hybrid-heterogeneous actuators: the aerodynamic surfaces, the vectored propellers and the buoyant ballonets. The aerodynamic surfaces have high efficiency in attitude control at high speed. However, vectored propellers are also introduced here for attitude control under the special working condition of low airspeed. Due to the lower thrust-to-weight ratio, the composite control of hybrid-heterogeneous actuators is the primary object in controller design for an airship. In composite attitude control, first the attitude moment allocation between aerodynamic control surfaces and vectored propellers is designed according to different dynamic airspeed, to achieve the smooth motion transition from low to high airspeed, then the weighted generalised inverse (WGI) is used to design the reconfigurable actuator allocation among the homogeneous multi-actuators, where the authority of every actuator can be decided by setting the corresponding value of the weight matrix, thus the control law is unchanged under different actuator configurations. Taking the mid-altitude airship as an example, the simulations of position control, trace tracking and altitude control are provided. Simulation results demonstrate that the attitude moments allocation obtains moment distribution between the aerodynamic surfaces and the vectored propellers under different airspeeds; the reconfigurable actuator allocation achieves a good distribution and reconfiguration among homogeneous actuators, thereby enhancing the reliability of the control system.